Effects of task oriented rehabilitation of upper extremity after stroke: a systematic review - Hussain, Maira; Arooj Fatima; Ashfaq Ahmad; Syed Amir Gilani (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the current scientific evidence on the effects of task-oriented rehabilitation programme of upper extremity post-stroke. Method: The systematic review comprised studies from 2012 to August 2020 which were both Hand-searched and explored on Cochrane, PubMed, PEDro and MEDLINE databases with authentic search techniques using population-intervention-control-outcomes format and Boolean operator. Randomised controlled trials on the use of task-oriented training for the improvement of upper extremity functional outcomes in subjects with stroke were shortlisted and reviewed. The risk bias tool was used to evaluate the biasness in the studies and the PEDro scale was used to evaluate the methodological quality of the studies. Results: Of the 28 articles assessed, 16(%) were included for detailed review. All studies varied significantly with PEDro scores between 6 and 10. There were 12(75%) high-quality studies and 4(25%) fell in fair category. All the studies showed significant results in the improvement of upper extremity after stroke through task-oriented training rehabilitation (p<0.05). Conclusion: Evidence supports the beneficial effects of task-oriented rehabilitation for the improvement of upper extremity functions post-stroke. Key Words: Conventional therapy, Stroke, Stroke rehabilitation, Task-oriented rehabilitation, Upper extremity paresis.